The Influence of Taxpayer Awareness and Tax Sanctions on Compliance with Land and Building Tax (PBB) Payments During the COVID-19 Pandemic in Surabaya - Khotimah, Khusnul; Wahyuni, Sri; Sadiqin, Amin (CV. Proaksara Global Transeduka, 2024)
The motivation behind this research stems from the need to compare the Regional Original Income (PAD) of Surabaya before and during the COVID-19 pandemic. It has been observed that there has been a decline in PAD gains during this period. The main objective of this study is to examine and analyze the impact of taxpayer awareness and tax sanctions on compliance with land and building tax payments. Non-compliance among taxpayers can be attributed to a lack of awareness and understanding of their tax obligations, as well as the consequences they may face. To gather data, the purposive sampling method was employed, which involved selecting participants based on specific criteria relevant to the study. The study analyzed questionnaires from 100 land and building taxpayers in Surabaya, collecting primary data. Hypothesis testing was conducted using multiple linear regression analysis with the SPSS program version 26. The findings revealed that both taxpayer awareness and tax sanctions had a significant positive influence on compliance with land and building tax payments when examined individually. Furthermore, when tested together, they also demonstrated a significant positive impact on compliance with these tax payments. Overall, this research provides valuable insights into the factors influencing taxpayer compliance with land and building tax payments in Surabaya. The findings highlight the importance of taxpayer awareness and the effectiveness of tax sanctions in promoting compliance. This information can be used by policymakers and tax authorities to develop strategies and interventions aimed at improving taxpayer compliance and increasing PAD gains.